Simulation analysis of the magnetic and thermal performance of large-capacity medium-frequency transformers and improvement in shielding structure - TIAN Fengqi; DU Zhenbin; WANG Jianmin; SHI Jian (Zhejiang dianli)
Large-capacity medium-frequency transformers （MFTs） offer advantages such as compact size， light weight， and high power density， but they also face significant challenges related to magnetic and thermal performance. To ensure the reliability of these transformers， a 100 MW level， 400 Hz MFT is selected for a simulation analysis of its magnetic and thermal performance. The electrical conductivity of the windings is first adjusted， and finite element software is then used to calculate and analyze the magnetic field distribution， loss density， and temperature field. The results reveal that leakage flux at the ends of the windings significantly impacts the structural components， leading to excessive stray losses and localized overheating. To address this， the limb-type magnetic shielding structure at the ends of transformer body is improved， with an analysis of how the dimensions of the shielding structure affect the magnetic and thermal performance of the components. A comparative analysis of the simulation results before and after these improvements shows a significant reduction in loss density and temperature rise in the structural components， ultimately ensuring that the magnetic and thermal performance meets design requirements.